Problem mocarstwowości Francji w ujęciu historycznym (do 1945 roku) - Pachocka, Marta (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2011)
In the early twenty-first century, France has the necessary geographic, geopolitical, demographic, economic, military (nuclear), political and cultural potential to be one of the most powerful states within the international system. Its position and capabilities are, however, questioned, while stressing only its desire to be a superpower. This article analyzes the international position of France in historical perspective (from the seventeenth century to 1945), assuming that this state is an example of the evolution from a global superpower to a regional power. In the first part of the article, the theoretical framework for the further analysis has been included, the attempts to define the concepts of the great power and superpower have been taken, the classifications of great powers have been presented and the factors determining the power of states have been identified. In the second part, the author shows the evolution of a great power status of France on a few examples from its history, referring to the reign of Louis XIV, the times of Napoleon Bonaparte and the rule of Napoleon III. In the third part of the article, the international position of the Third French Republic is discussed, with particular emphasis on its foreign policy, including colonial one, since the 1870s to the German invasion in June 1940. The effects of World War II for its position in the international system are also described. The author concludes that France was a global superpower in two historical moments (the absolute monarchy of Louis XIV and the French Empire of Napoleon I), and is now a regional power with global interests.